A Brief Review on Multimedia-Based Health Education Applications: Current Trend and Future Potential - Pei Lin, Lua; Nor Khaira Wahida, Khairuzzaman (2014)
Objective: This paper intended to review and analyse relevant published articles which have studied or applied multimedia as the educational medium for patients or their caregivers. The benefits were also recorded. Method: The search was performed across the databases EBSCO Host, Springer Link, Science Direct and PubMed for relevant studies. Only full-text articles using English as a language of publication were included. Eligible articles included any usage of multimedia intervention as health information delivery for patients or caregivers. No restriction for publication date was set to permit a wider capture. Result: Twenty articles met the inclusion criteria resulting in the involvement of a total of 5,760 respondents. The studies have been conducted in various countries mostly in the North American region followed by Europe. The focused disease for each study varied from asthma to cognitive impairment but most were on cancer. Problems in caregiving and depression were also reported. The overall data suggested that the multimedia-based education had generated modest improvement in self-efficacy, patient satisfaction, coping drills, and perceptions of social support. Cost benefits were also recorded. Additionally, patients' behavioural changes were well maintained in parallel with the intervention programme. Conclusion: The evolution of multimedia as an educational medium is growing and its incorporation has benefited health education management especially in improving patients' and their family's psychosocial outcomes. However, due to still limited scientific evidence to support its value, further multimedia-based interventions should be developed out of the need to share information and knowledge among patients as well as caregivers.